A measure of ionospheric irregularities: zonal velocity and its implications for L-band scintillation at low-latitudes - Cesaroni, Claudio; Spogli, Luca; Franceschi, Giorgiana De; Damaceno, Juliana Garrido; Grzesiak, Marcin; Vani, Bruno; Monico, Joao Francisco Galera [UNESP]; Romano, Vincenzo; Alfonsi, Lucilla; Cafaro, Massimo (Earth and Planetary Physics, 2021)
We estimate the zonal drift velocity of small-scale ionospheric irregularities at low latitude by leveraging the spaced-receivers technique applied to two GNSS receivers for scintillation monitoring installed along the magnetic parallel passing in Presidente Prudente (Brazil, magnetic latitude 12.8°S). The investigated ionospheric sector is ideal to study small-scale irregularities, being located close to the expected position of the southern crest of the equatorial ionospheric anomaly. The measurement campaign took place between September 2013 and February 2014, i.e. equinox and summer solstice seasons under solar maximum, during which the probability of formation of small-scale irregularities is expected to maximize. We found that the hourly average of the velocity increases up to 135 m/s right after the local sunset at ionospheric altitudes and then smoothly decreases in the next hours. Such measurements are in agreement with independent estimations of the velocity made by the Incoherent Scatter Radar located at the Jicamarca Radio Observatory (magnetic latitude 0.1°N), by the Boa Vista Ionosonde (magnetic latitude 12.0°N), and by applying a recently-developed empirical regional short-term forecasting model. Additionally, we investigated the relationship with the percentage occurrence of amplitude scintillation; we report that it is exponentially dependent on the zonal velocity of the irregularities that cause it.
Keywords: Equatorial Plasma Bubbles; GNSS; ionospheric irregularities; low-latitude ionosphere; plasma drift velocity; scintillation; spaced receivers